Notes on Campylocentrum (Vandeae; Epidendroideae; Orchidaceae): Re-establishment of two South American species - Pessoa, Edlley M.; Alves, Marccus (Phytotaxa, 2015)
During research for a taxonomical review of Campylocentrum, two South American species, C. kuntzei, described from Bolivia, and C. mattogrossense from Brazil, previously considered synonyms of Campylocentrum micranthum or C. robustum, were recognized as distinct species. This study reinforces the significant morphological differences among the taxa and proposes their re-establishment. Descriptions and illustrations, in addition to typifications, new synonyms, an identification key and their conservation statuses are provided.